Pengembangan SMS Gateway Layanan Informasi Akademik di STMIK GI MDP - Fithri Selva Jumeilah; Fransiska Prihatini Sihotang (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2017)
Information technology can be utilized in education such as e-Learning and Academic Information System. STMIK GI MDP has applied information technology that provides ease for the dissemination of academic information to students. However, the parents of the students have not obtained the academic information of their children due to the lack of internet-related knowledge. Therefore, this study aims to create a service that is able to convey information to parents directly with SMS Gateway service. This research begins with the collection of user needs through observation techniques and interviews to academic staff and parents. Then performed the required feature analysis. Then the design of SMS Gateway application that will be embedded in existing academic applications and coding system. Gammu is used as a link between applications with mobile phones. The result of this research is the application of SMS Gateway service that can give the student academic information to the parents.